Learning Chemistry Through Project: The Impact of STEM – Based Project Learning on Students’ Mastery of Natural Acid- base Indicators - Selvirna, Hilka Yovi; Kurniasih, Dedeh; Fadhilah, Raudhatul (Education, Science, and Technology International Conference, 2025)
The low student achievement in acid–base material at SMAN 9 Pontianak highlights the need for an innovative learning approach that promotes active student engagement and strengthens conceptual understanding. Previous studies have shown that the Project-Based Learning (PjBL) model can improve students’ conceptual understanding when integrated with the STEM (Science, Technology, Engineering, and Mathematics) approach. This study aims to analyze the effect of the STEM-based PjBL model on improving student learning outcomes. A quantitative approach was used with a quasi-experimental design of the Nonequivalent Control Group Design type. The sample was selected using purposive sampling, resulting in 74 eleventh-grade students out of 246, divided into a control group (demonstration method) and an experimental group (PjBL-STEM), each consisting of 37 students. The research instruments included validated pretest and posttest questions. Data were analyzed using normality tests, homogeneity of variance tests, independent sample t-tests, and effect size calculations. The results showed a significant difference between the two groups, with an effect size of 2.085, which falls into the high category. These findings indicate that the implementation of the STEM-based PjBL model significantly improves student learning outcomes and is effective in developing critical thinking skills and understanding of chemistry concepts. Therefore, the STEM-based PjBL model can be considered a strategic alternative in chemistry education.